Iluminación con tecnología led para la cancha de fútbol del corregimiento de Cornejo Norte de Santander (2020)
The integral Work of degree consisted in the projection of the lighting system using LED technology for the soccer field of the township of Cornejo, the municipality of San Cayetano, north of Santander, Colombia. During the development of this project, the current regulations that the country has implemented through the responsible entities such as the CREG Commission for Energy Regulation, as well as the Colombian electrical regulations that govern the use of electrical products, were taken into account. photovoltaic, its technical specifications, compliance with the RETIE electrical regulation. This photovoltaic system will generate the electrical energy consumed by the LED technology lighting system of the soccer field located in the Cornejo district, creating long- term energy consumption savings for approximately 25 years of the useful life of these solar panels and therefore economic benefits for the mayor of the municipality of san Cayetano. The methodological projection in the construction of a photovoltaic solar system was carried out step by step, starting from the statistical analysis of climatological variables in the township of Cornejo using IDEAM statistics, which must be taken into account for any renewable energy project. , the ambient temperature, the solar radiation, the solar brightness, the relative humidity and the wind speed in the different months of the year